Using pest monitoring data to inform the location and intensity of invasive-species control in New Zealand. (November 2015) - Ruffell, Jay; Innes, John; Bishop, Craig; Landers, Todd; Khin, Jade; Didham, Raphael K.
Abstract: Improving decision-making about where and how invasive species management is conducted requires a better understanding of spatial variation in pest abundance and the extent to which different pest control regimes reduce those abundances. We measured how the relative abundance of invasive rats and possums, indexed at 147 forest sites in northern New Zealand, varied in response to environmental variables, and to the category of pest control at the site: no control (NC), periodic possum (PP), low-intensity rat and possum (LRP), and high-intensity rat and possum (HRP). We found that climate and topography strongly influenced the rat index, while vegetation characteristics strongly influenced both indices. These variables may therefore be useful for predicting pest impacts and prioritising locations for pest control. HRP control substantially reduced pest abundance indices, with model-predicted values for the rat index that were 99% lower than in areas of no control, and 91% lower for the possum index. In contrast, indices did not differ significantly among NC, PP, and LRP. PP and LRP regimes dominate pest control in New Zealand, but may be of limited conservation value, at least in terms of the 'average' operation in our study region. Globally, conservation agencies with limited budgets frequently avoid monitoring pest populations, since resources spent on monitoring are no longer available for management. However, our results highlight the value of collecting and analysing pest monitoring data, both for informing the location of future management and for ensuring that scarce resources are not wasted on ineffective control. Highlights: Rat and possum abundances were related to pest control and environmental variables. High-intensity control substantially reduced rat and possum abundances. Low-intensity control dominates pest management but had no measurable effect. Environmental variables can help to prioritise pest control locations. Pest monitoring may ensure that scarce resources are not wasted on ineffective control.